The formation problem of the Tatar class in the Kazan Khanate (specific historical and theoretical aspects) - Iskhakov D.M. (Золотоордынское обозрение)
The purpose of the study: Despite the publication of a significant number of works on the history of the Kazan Khanate, including the rethinking of old approaches to the study of the feudal class of this state, directly related to the Golden Horde Tatars, the problem of the formation and development of this state-forming stratum, which ascended in the Kazan yurt to the Tatars of Bulgar Vilayet Ulus Jochi, is still far from a final consensus. In this study, we focused on the analysis of the entire complex of issues related to the formation of the Tatar layer of the state that controlled it, and also on how both in the Kazan Khanate and in its political predecessor in the person of the Bulgar Vilayet, the ruling class was built on a clan basis. The system of power itself was based on the institution of Karacha-beks. The system of Karacha-beks, originally based on 4 leading clans, existed both in the Bulgar vilayet and in the Kazan Khanate, although the composition of the ruling clans in them differed. But in order to reveal the peculiarities of the clan composition of these two polities, a detailed – as far as the sources allow – analysis of the totality of information regarding the clans present there was carried out. In addition, the question of the ratio of nomadic and settled economy among the Tatars of the Kazan Khanate was also clarified. Research materials: the data of Russian chronicles, the Tatar source “Daftar-i Chingiz-name”, the works of Utemish-hadzhi, Abdulgaffar Kyrimi, Kadyr Ali-bek, materials of diplomatic correspondence of the 16th century, epigraphic materials, historical legends, and genealogical data were used in the work, associated with noble Tatars.Results and novelty of the study: The study showed that the Kazan Khanate did not inherit the former clan composition of the Tatar population of the time of the Bulgar vilayet, it was different, characteristic of the right wing of the Golden Horde and later the Greater Horde-Crimean polity. In addition, research of issues related to the formation of the Tatar stratum (estate) of the Kazan Khanate made it possible to formulate a hypothesis that it partially continued to lead a nomadic lifestyle throughout the entire period of the existence of this yurt, being in a complex interaction with the Tatars of the Nogai Horde. That allows us to take a new look in general at the question of the formation of the ethnic community of the “Kazan Tatars”, including such aspects as its territorial borders.